Types and Abundance of Microplastics in Meretrix meretrix Clams and Sediments in the Sri Tanjung Coastal Area, Rupat Sub-District, Bengkalis - Lestari, Tri; Amin, Bintal; Efriyeldi, Efriyeldi (Jurnal Perikanan dan Kelautan, 2025)
This study was conducted in August 2024 in the coastal area of Sri Tanjung Village, Rupat Sub-district, Bengkalis Regency. The objectives of this research were to identify the types and abundance of microplastics, examine the differences in microplastic abundance across sizes, analyze the relationship between microplastic abundance and size (shell length and total weight), and explore the relationship between microplastic abundance in Meretrix meretrix clams and sediments. A survey method was used. Random sampling of M. meretrix was carried out using small shovels and traditional fisher tools (iron rakes) during the lowest tidal conditions. Results indicated that water quality parameters in Sri Tanjung were relatively good, with temperatures of 28–31°C, salinity ranging from 21–26%, brightness values between 19–25 cm, and pH values of 7–7.7. Types of microplastics found in M. meretrix and sediments in the coastal area included fragments, fibers, and films, with an average microplastic abundance of 55.16 particles/g and 1310 particles/kg, respectively. The abundance of microplastics was categorized based on the morphometric size of clams: small (61.32 particles/g), medium (45.01 particles/g), and large (59.16 particles/g). Sediments showed an average abundance of 1310 particles/kg. Fragment-type microplastics were the most dominant in both clams and sediments, with average abundances in small clams (29.22 particles/g), medium clams (21.29 particles/g), large clams (62.27 particles/g), and sediments (541.3 particles/kg). Film-type microplastics were the least abundant, with average values in small clams (14.44 particles/g), medium clams (10.80 particles/g), large clams (13.05 particles/g), and sediments (319.3 particles/kg). A one-way ANOVA test revealed significant differences (p < 0.05) in microplastic abundance between small and medium and medium and large clams but not between small and large clams (p > 0.05)